Pharmacokinetic study for the establishment of bioequivalence of two inhalation treatments containing budesonide plus formoterol. (11th August 2014) - Grekas, Nikolaos; Athanassiou, Katerina; Papataxiarchou, Katerina; Rizea Savu, Simona; Silvestro, Luigi
Abstract Objectives The aim of this study was to compare lung deposition and assess the bioequivalence of two formulations containing budesonide and formoterol and being delivered via Elpenhaler and Turbuhaler, respectively. A pharmacokinetic (PK) study was conducted. Methods An open, randomized, two‐sequence, two‐period, crossover, single‐dose study in 100 asthmatic patients under fasting conditions was performed. Wash out period was 6 days. Equivalence in lung deposition was assessed after a single inhalation of each treatment with concomitant oral administration of activated charcoal (40 g) to prevent gastrointestinal absorption of the drugs. Several PK parameters were estimated, the area under the drug concentration in plasma versus time curve (AUC0−t) and the maximum drug concentration in plasma (Cmax) being the primary response variables. Equivalent lung deposition was concluded if the 90% confidence interval (CI) for the Elpenhaler/Turbuhaler geometric mean ratio of AUC0−t and Cmax, for both drug substances fell within the regulatory limits (0.80–1.25). Key findings Acceptance criteria were met. Equivalent lung deposition can be concluded. No statistically significant differences between treatments in the incidence of adverse events were found. Conclusions The formulations are bioequivalent regarding both rate and extent of absorption. The treatments were also well tolerated by the participating subjects.